THE EFFECT OF AUDIT QUALITY AND COMPANY'S FINANCIAL CONDITION ON GOING CONCERN AUDIT OPINION AT THE REGIONAL PUBLIC ACCOUNTING OFFICE OF DKI JAKARTA - Eko Cahyo Mayndarto (LPPM Press STIE Indragiri Rengat, 2022)
The survival of the company is always associated with the ability of management to manage the company in order to survive. Going concern is the ability of a business unit to maintain its viability for a reasonable period of time, which is no more than one year from the date of the financial statements, and the role of the auditor is also responsible for the going concern audit report. Statistical tests are used to provide an overview and description of the variables to be studied. This analysis can also be seen from the average value (mean), standard deviation, variance, maximum, minimum, sum, range, kurtosis and skewness (skew of distribution). Therefore, in this study, information will be obtained about the relationship between variables after all data is collected, and will be processed and presented in the form of data tables. The results obtained from descriptive statistics cannot be used to find conclusions broadly. The influence of Audit Quality and the Company's Financial Condition simultaneously affects the Going Concern Audit Opinion at the Public Accounting Firm in DKI Jakarta. This is indicated by the value of Adjust R Square, which means that the dependent variable of Going Concern Audit Opinion is simultaneously influenced by the independent variables in this study, namely Audit Quality and Company Financial Condition. From the calculation results of the SPSS Version 25 program the influence of Audit Quality on Going Concern Audit Opinions shows the value of sig. In this study, the results of data analysis obtained R Square (R2), which means that the Going Concern Audit Opinion at the DKI Jakarta Public Accounting Firm is influenced by Audit Quality and the rest is influenced by other variables that are not included in this study.